Correlation of microsegregation and variant distribution in directionally solidified Ni-Mn-Ga alloys. (November 2018) - Hou, Long; Dai, Yanchao; Fautrelle, Yves; Li, Zongbin; Ren, Zhongming; Esling, Claude; Li, Xi
Abstract: In this work, the microsegregation and variant distribution in directionally solidified Ni-Mn-Ga alloys have been investigated. The results show that the martensitic variant distribution changed dramatically, as well as a decrease in microsegregation between dendrite core and interdendritic regions, after the directionally solidified samples underwent a high-temperature heat treatment. Further theoretical calculations reveal that the preferential martensitic configuration is accommodated with martensitic-transformation-induced stress in the Ni-Mn-Ga alloys with pronounced microsegregation. This finding is of significance as it highlights the role of microsegregation in variant distribution and provides a possible way to obtain martensite with a controllable variant distribution. Graphical abstract: Unlabelled Image